Effect of the Management Devolution Process on the Technical Efficiency of Public Health Facilities in Nakuru and Baringo Counties of Kenya - Aggrey Lihanda Mwandihi; Irene Asienga (Editon Consortium Journal of Economics and Development Studies, 2026)
This study investigated the effect of the management devolution process on the technical efficiency of public health facilities in Nakuru and Baringo Counties, Kenya. Despite increased government expenditure, the public health sector continues to experience inefficiencies. Guided by Principal-Agent Theory, the study conceptualised national and county governments as principals and health personnel as agents responsible for implementing policies, managing resources, and delivering healthcare services. Management devolution was measured using performance contracting, Health Management Boards (HMBs), and Health Management Teams (HMTs). A quantitative descriptive research design was employed, targeting 3,199 employees from 401 Level 4–5 public health facilities in the two counties. Using Slovin’s formula, a proportionate sample of 355 employees was selected. Primary data were collected using structured questionnaires and analysed using SPSS version 27. Technical efficiency was assessed using descriptive statistics, including frequencies, means, and standard deviations. The findings revealed a moderate positive and statistically significant relationship between management devolution and technical efficiency (? = 0.256, t = 5.220, p < 0.001). The findings suggest that strengthening management devolution through enhanced decision-making authority, planning, supervision, and performance management can improve technical efficiency in public health facilities. The study recommends that county health authorities strengthen Human Resource for Health management through adequate funding, strategic recruitment, and equitable staff deployment to address workforce gaps and enhance service efficiency.